Response of Weeds and Yield of Dry Direct Seeded Rice to Tillage and Weed Management - Jagat Devi Ranjit; Rungsit Suwanketnikom (Agriculture and Natural Resources, 2005)
The study was initiated to assess the performance of rice (Oryza sativa) under dry direct seeded environment with two tillage systems of conventional tillage and minimum tillage and five weed management treatments namely unweeded control, handweeding twice 25 and 45 days after seeding, anilophos + one handweeding, bispyribac-sodium, and straw mulch + bispyribac-sodium as an alternate method of transplanting in the mid-hill ecology. Both anilophos and bispyribac–sodium were found to reduce narrowleaf and broadleaf weeds compared to unweeded control. However, anilophos reduced Cyperus difformis, C. sanguinolentus, and C. iria 4 weeks after seeding (WAS) but not Ammania sp. and Dopatrium junceum 8 WAS. Bispyribac–sodium and straw mulch + bispyribac-sodium reduced the population of Alternanthera philoxeroides, Ammania sp., Commelina diffusa, C. difformis, C. iria, and D. junceum 8 WAS. No phytotoxic effect on the rice plants was observed due to both herbicides. Yield and yield attributes were not affected by the tillage systems. The weed managements were found to affect the numbers of tiller per square meter and grain yield. The increasing number of weed did not affect the plant height of rice (Khumal-4). The numbers of tiller and grain yield highly affected the increasing number of weed population. Anilophos plus one handweeding, straw mulch plus bispyribac-sodium, handweeded twice and bispyribac–sodium alone gave higher yield compared to unweeded control. Promising grain yield could be achieved with the anilophos or bispyribac-sodium with additional physical or mechanical control methods in dry direct seeded rice.